PENGARUH KEMANDIRIAN BELAJAR DAN PENGGUNAAN AI CHATGPT TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SMK MAHARDHIKA SURABAYA JURUSAN MANAJEMEN PERKANTORAN - Faqih Febriyanto, Reiza; Farida Panduwinata, Lifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The shift in artificial intelligence (AI) from automation tool to cognitive partner demands its use to strengthen critical reasoning, not just broaden information access. In vocational high schools (SMK), especially Office Management, critical thinking is vital for accurate administrative decision-making. Observations at SMK Mahardhika Surabaya revealed students often relied on internet searches without explaining the reasoning behind their answers, possibly due to low self-regulated learning. This study aimed to analyze the effects of self-regulated learning and AI ChatGPT usage on critical thinking skills. An explanatory quantitative approach was used with a sample of 158 students selected via proportional random sampling. Data were collected through questionnaires and analyzed using multiple linear regression. Results showed: (1) self-regulated learning positively and significantly influenced critical thinking (β=0.492; p<0.05); (2) AI ChatGPT usage also had a positive significant effect (β=0.281; p<0.05); and (3) simultaneously, both contributed 26.6% (F=28.066; p<0.05). Self-regulated learning had a larger contribution. These findings confirm that integrating ChatGPT in learning is optimal when supported by strong self-regulated learning, enabling students to use AI as a tool for exploration and evaluation rather than an instant answer source.